The Multiple Faces of Spinocerebellar Ataxia type 2. Issue 9 (10th August 2017) - Antenora, Antonella; Rinaldi, Carlo; Roca, Alessandro; Pane, Chiara; Lieto, Maria; Saccà, Francesco; Peluso, Silvio; De Michele, Giuseppe; Filla, Alessandro
Abstract: Spinocerebellar ataxia type 2 (SCA2) is among the most common forms of autosomal dominant ataxias, accounting for 15% of the total families. Occurrence is higher in specific populations such as the Cuban and Southern Italian. The disease is caused by a CAG expansion in ATXN2 gene, leading to abnormal accumulation of the mutant protein, ataxin‐2, in intracellular inclusions. The clinical picture is mainly dominated by cerebellar ataxia, although a number of other neurological signs have been described, ranging from parkinsonism to motor neuron involvement, making the diagnosis frequently challenging for neurologists, particularly when information about the family history is not available. Although the functions of ataxin‐2 have not been completely elucidated, the protein is involved in mRNA processing and control of translation. Recently, it has also been shown that the size of the CAG repeat in normal alleles represents a risk factor for ALS, suggesting that ataxin‐2 plays a fundamental role in maintenance of neuronal homeostasis.